PERBEDAAN KONTROL GLIKEMIK (HBA1C) BERDASARKAN SELF- EFFICACY PASIEN DM TIPE 2 DI KLINIK DOKTER KELUARGA YOGYAKARTA - , IRENA SANDRADEWI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Introduction: The efficient DM medication required alteration of decision and daily habitual that includes nutrient, physical activity, drugs, blood glucose monitoring, and stress management. The complexity of the DM management involves the difficulty of the patient to conduct self-management. Self-efficacy is one of the dominant concept to support self-management of DM patient. Method: The research was designed by quantitative non-experimental with cross sectional analysis planning. The population were DM patient at family dispensary Yogyakarta (DK). The number of samples was determined by purposive sampling and there were 33 peoples that fell into that category. The collection of data was engaged by DMSES questionnaire and analyzed by using independent T-test with p<0.05 significant. Result: The research showed that there was a significant difference (p value 0,014, Î±: 0, 05) of glycemic control based on self-efficacy on DM type 2 patient. Conclusion: There was a significant difference of glycemic control based on self-efficacy in DM Patient. Keyword: Self-efficacy, Diabetes Mellitus type 2, glycemic control, HbA1c